Analisis Dan Perancangan Jaringan Komputer Sekolah Dasar Islam Sains Dan Teknologi Ibnu Qoyyim Surakarta - Yunus Irawan; Abdillah Baraja (Indonesian Journal of Networking and Security (IJNS), 2012)
Abstact : The development of technology at this present and many people needs data  processing  and the organization or educations institution for their daily activities as well. It can not separated from the computer technology which can assist and provide data management and storage easy. In an organitation such as educational institutions at all times conduct activities related to processing and storage data, it is necessary  a communication system where the data need to be processed, data storage and exchage of  information between each other can be done quickly and efficiently. The Elementary School  of  Sains and Technology  which is  located in Gajah Mada Street ,  Banjarsari Surakarta region have not apply integrated computer  network system. The data collection conducted be teacher  from one computer to another computer has many obtacles. This is because computers are not able to make sharing data  and as well as  some importants data storage in each teacher’s notebook  privately.  The design is made, because of the difficulty of retrieval of  data from one computer to another. With this design, we hope that the teacher  can retrieve the data easier.   The design aims is to make a planning of computer network system design. The research methodology used  observation, literature, interviews, analysis, planning. The results of this design is expected to give reference and tools for  the  School of Science and Technology Surakarta to build the computer network system design easy to implement  in near the future.   Keyword : computer  network , sharing data